Development Of An Indonesian Student Fitness Test Application In Supporting The Design Of A National Sports Great In East Kalimantan - Didik Cahyono; Muhammad Sukron Fauzi; Wafik Azizah; Sindi Amelia (CV. AFDIFAL MAJU BERKAH, 2023)
The aim of this research is to make it easier for teachers to implement fitness tests for Indonesian students in the East Kalimantan region, as well as to produce an application for the Indonesian Student Fitness Test to support the grand design of national sports in East Kalimantan. To find out the effectiveness of this application as a medium for implementing fitness tests for Indonesian students. In this research, the development media used is the procedural development model, because this model is descriptive, namely a procedure that outlines the steps that must be followed in producing a product. The validation score results from media experts on the product as a whole aspect are